Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $f \circ g$ is invertible, is $(f \circ g)^{-1} = g^{-1} \circ f^{-1}$?

If not can someone give me a counterexample?

share|cite|improve this question
A formula which "works" on the real line is $f=\frac 1 x$, but this is not a function as it is undefined at $x=0$. The question does not specify what kinds of objects $f \text{ and } g $ are supposed to be. Precision of language would be easier to specify if the question were more precisely stated. – Mark Bennet Jun 25 '12 at 7:08
Also see – Babak S. Jun 25 '12 at 7:13
up vote 13 down vote accepted

It is true if $f$ and $g$ are invertible. You can check this directly by using the definition of inverse function.

But neither $f$ nor $g$ need to be invertible for $f\circ g$ to be invertible. To find a counterexample, I suggest looking for a noninjective $f$ and a nonsurjective $g$.

share|cite|improve this answer
I want to add this point to Jonas answer that we should have: $f:A\longrightarrow B$ and $g:B\longrightarrow C$ wherein $A,B$ and $C$ are sets. :) – Babak S. Jun 25 '12 at 7:06

Let $ f:\{0,1\} \rightarrow \{0\} $ be defined by $ f(0) = 0 = f(1) $

and define $ g:\{0\} \rightarrow \{0\} $ with obvious mapping $g(0) = 0$

then $ f \circ g $ is defined from $ \{0\} $ to $ \{0\} $ with $ (f \circ g) (0) = 0 $ and $ (f \circ g)^{-1} (0) = 0 $

but f is not invertible.

share|cite|improve this answer

In my view. I think if we take them as binary relations, then we would have

$g^{-1} \circ f^{-1}$

=$\left \{(z,x) \in \operatorname{dom}(f^{-1}) \times \operatorname{ran}(g^{-1})|\exists y \in \operatorname{ran}(f^{-1}) \cap \operatorname{dom}(g^{-1})((z,y) \in f^{-1}\land(y,x) \in g^{-1})\right \}$

=$\left \{(z,x) \in \operatorname{ran}(f) \times \operatorname{dom}(g)|\exists y \in \operatorname{dom}(f) \cap \operatorname{ran}(g)((y,z) \in f\land(x,y) \in g)\right \}$

=$\left (\left \{(x,z) \in \operatorname{dom}(g) \times \operatorname{ran}(f)|\exists y \in \operatorname{dom}(f) \cap \operatorname{ran}(g)((y,z) \in f\land(x,y) \in g)\right \}\right )^{-1}$

=$(f\circ g)^{-1}$

That means $g^{-1} \circ f^{-1}=(f\circ g)^{-1}$ always holds regardless of whether they are invertible functions

For the direct proof of invertible function. We need to prove

  1. $dom((f \circ g)^{-1})=dom(g^{-1} \circ f^{-1})$

  2. for all $z \in dom((f \circ g)^{-1})$, $(f \circ g)^{-1}(z)=g^{-1} \circ f^{-1}(z)$


(1) Suppose that $z \in dom((f \circ g)^{-1})$, let $x=(f \circ g)^{-1}(z)$. Then $f \circ g(x)=z$. Hence $f^{-1}(z)=g(x)$. Consequently $g^{-1} \circ f^{-1}(z)=x$. Therefore $z \in dom(g^{-1} \circ f^{-1})$.

Suppose that $z \in dom(g^{-1} \circ f^{-1})$, let $x=g^{-1} \circ f^{-1}(z)$, analogously $x=(f \circ g)^{-1}(z)$.

Therefore $dom((f \circ g)^{-1})=dom(g^{-1} \circ f^{-1})$.

(2) According to the proof of (1) $g^{-1} \circ f^{-1}(z)=(f \circ g)^{-1}(z)$ for all $z$ in the domain of $(f \circ g)^{-1}$.


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.